2015
DOI: 10.24127/gdn.v5i1.55
|View full text |Cite
|
Sign up to set email alerts
|

Profile of High Touch in the Application Learning Process

Abstract: This research generally aims to get brief description of application high touch in learning process. This research is conducted by descriptive quantitative method. The population is all teachers and students at senior high school. Samples are taken by using stratified cluster random sampling technique. The percentage, correlation and t test. The results of this research reveal that application high touch in learning process less and teachers' opinion about high touch implementation as implication of teachers' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…These results are supported by the results of research conducted by Sin (2010) that high-touch implementation is in a good category. This was also supported by Mashari (2015) who found that in general teachers have implemented authority in the learning process both in the opinion of the teacher and in the opinions of students.…”
Section: High-touch Teacher Implementationmentioning
confidence: 59%
“…These results are supported by the results of research conducted by Sin (2010) that high-touch implementation is in a good category. This was also supported by Mashari (2015) who found that in general teachers have implemented authority in the learning process both in the opinion of the teacher and in the opinions of students.…”
Section: High-touch Teacher Implementationmentioning
confidence: 59%
“…Proses pembelajaran pada dasarnya tidak dapat dilepaskan dari pemaham pendidik tentang perserta didik [14]. Keberhasilan pendidikan tidak hanya tergantung pada pendidik yang selalu dituntut dapat mengajar secara profesional saja, malainkan peran aktif siswa didalam proses belajar juga sangat menentukan keberhasilan proses pendidikan [15].…”
Section: Pendahuluanunclassified
“…Kedua memberikan panduan umum tentang prosedur pembelajaran yang cocok untuk setiap tahap perkembangan sehingga pendidik dapat merancang dan menerapkan metode pembelajaran yang sesuai dengan kemampuan dan kebutuhan siswa pada setiap tahap perkembangan (Mustikaati et al, 2023). Ketidaktahuan seorang pendidik terhadap peserta didik dapat mengakibatkan praktik pembelajaran yang tidak memberikan kesempatan maksimal bagi pengembangan potensi siswa yang berdampak pada potensi siswa yang terabaikan, terbengkalai, dan bahkan terhambat untuk berkembang secara optimal (Mashari, 2015).…”
unclassified